The estimation of the value and mobility of Parks' angle in case-series of patients with defectory disorders - prospective clinical examination supplemented with the defecographic examination - Kołodziejczak, Małgorzata (Radiology and oncology (Ljubljana), 2006)
Background. Defecography is used by a majority of colorectal surgeons for it is the only method for anatomic and dynamic studies of the act of defecation. The method provides information on different aspects of anorectal and pelvic floor function and offers the possibility of visualizing the development of anatomic abnormalities. Methods. We analyzed the defecography findings carriedout at 56 patients (50 female and 6 male) from 24 to 83 years of age (the average age 58.3 years) with proctologic ailments such as: faecal incontinence, sensation of obstruction in the rectum, constipations, rectal prolapse, solitary ulceration of rectum. The values of Parks' angle (ARA - theanorectal angle) were measured at rest, at strain and during defecation. Other parameters measured included: duration of sphincter relaxation, overall duration of defecation, mobility of the pelvic diaphragm. Results. Abnormal values of Parks' angle at rest and at strain were found in patients with the following problems: faecal incontinence, sensation of obstruction in rectum and constipation. However, they did not turn out to be characteristic for patients with rectal prolapse. Defecography has helped to detect concomitant rectocele in patients suffering from constipation and sensation of obstructionin the rectum. Defecography has also proved to be effective in the evaluation of patients who suffered from solitary ulceration of rectum. Duringthe examination of these pah'ents it has been observed that Parks' anglein various phases of defecation has flattened. The duration of sphincter relaxation in the studied group was changeable and did not depend on the kind of pathology. Conclusions. Defecography is one of the examinations which can be helpful in the evaluation of patient's motor functions both before and after the operation.
Keywords: Constipation; Contrast Media; črevesne bolezni; defektografija; diagnostika; Fecal Incontinence; Fekalna inkontinenca; iztrebljanje; Kontrastna sredstva; metode; Obstipacija; Radiography; Rectal Prolapse; Rectum; Rektum; Rektum, prolaps; Ulcer; Ulkus; Video, snemanje; Videotape Recording